Deconstructing the LGBT-Victimization Association: The Case of Sexual Assault and Alcohol-Related Problems - Felix, Shanna N. (2015)
Research on lesbian, gay, bisexual and/or transgender (LGBT) students has been gaining traction in the fields of criminology, victimology, and education, but available data lag behind the demand for studies on this underserved population. While LGBT students are often perceived to face greater risk of victimization and subsequent health problems than their counterparts, little research has investigated the mechanisms behind problematic outcomes for LGBT students. This research uses data from a Southeastern University to examine sexual assault among LGBT students and their experiences with alcohol-related problems. The results show that LGBT youth are at an increased risk for sexual victimization but that LGBT status does not have a direct effect on alcohol-related problems